Real-time Application and Statistical Evaluation of Reservoir Operating Rules Under Inflow Uncertainty in Monte Carlo Simulations - Muhammad Mujiburrakhman; Rachmad Jayadi; Istiarto; Indra Nurdianyoto (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Reservoir Operating Rules (ROR) have been well-known in Indonesia as guidelines for reservoir operation that comprise the release rules and rule curves derived from the dependable inflow time series in dry, normal, and wet conditions. However, likely because of the incoherence of the original application concept of ROR, the real performance of ROR in reservoir operation has so far remained unclear. This paper proposes a practical application concept of ROR and evaluates the performance of its implementation for annual storage conservation and periodic demand satisfaction under inflow uncertainty in the integrated system of Segawe Regulating Weir, Wonorejo Multipurpose Dam, and Tiudan Regulating Dam. The release rules for the three hydraulic structures were integrated into a unified “Wonorejo ROR”throughoptimization of water allocation over 36 ten-day operational periods. The performance of the application of Wonorejo ROR was evaluated based on several operational success and failure events in Monte Carlo simulations, for which 1,000 years of unique and independent synthetic inflow time series were generated from the Thomas–Fiering model. Under the application concept of ROR, the release decisions for the three hydraulic structures were made in real-time solely based on the actual water level of Wonorejo Reservoir and the rule curves of Wonorejo ROR. For comparative purposes, the Monte Carlo simulations were carried out to evaluate two alternatives of Wonorejo ROR, namely ROR-D65 and ROR-D80, which had different dry inflow exceedance probabilities. Based on the specified events in the Monte Carlo simulations, ROR-D65 and ROR-D80 resulted in reliabilities of 76.4% and 81.3% for annual storage conservation, and the lowest reliabilities of 73.9% and 52.4% for periodic demand satisfaction, respectively. In addition, other reservoir operational performancesandacomprehensive interpretation oftheproposed applicationconcept of ROR arepresented in this paper.